A novel wind resistance sliding support with large sliding displacement and high tensile strength for metal roof system. (15th September 2021) - Min, Qiaoling; Li, Ning; Zhang, Yongji; Lu, Qiaorong; Liu, Xudong
Highlights: Sliding support with large sliding displacement and high tensile strength for metal roof system is proposed. Experimental test and numerical analysis results of the novel wind resistant sliding support were presented. Large displacement and high tensile strength capacity was illustrated and compared with original designed support. Wind loading capacity of a metal roof system using new support is calculated and illustrated for demonstration. Abstract: The metal roof is widely used in large-span spatial structures for its lightweight. However, the traditional rivet connection cannot effectively handle the large deformation caused by the temperature effect. In traditional sliding supports, the metal roof tears and the roof lifts due to insufficient sliding displacement or low tensile strength, which reduces the service life of the metal roof system. To solve this problem, a new sliding support was proposed by changing the structure of the traditional sliding supports. The model experiments were performed to attain the tensile strength and eccentric mechanical properties. Afterward, a numerical simulation was adopted to investigate the corresponding performance of the proposed sliding support. A quantitative model of the relationship between the eccentric distance and the ultimate tensile strength was established to attain the true strength when the supports are installed at different positions of the roof. For structures, the wind load capacity and failure modes of metal roof systems with different sliding supports were simulated and investigated. The results showed the preference of the proposed sliding support over the traditional one. Compared to the traditional sliding support, the sliding displacement of the proposed sliding support was increased by 2.0–3.24 times and the ultimate tensile strength was increased by 3.14–3.87 times. Therefore, choosing the proposed sliding support instead of traditional rivet connections provides a more flexible and suitable way for large-span structures. Thus, the proposed sliding support is a promising connection in civil engineering.